Tissue specific innate immune responses impact viral infection in Drosophila. - Elisha Segrist; Steven Miller; Beth Gold; Yue Li; Sara Cherry (PLoS Pathogens)
All organisms sense and respond to pathogenic challenge. Tissue-specific responses are required to combat pathogens infecting distinct cell types. Cyclic dinucleotides (CDNs) are produced endogenously downstream of pathogen recognition or by pathogens themselves which bind to STING to activate NF-kB-dependent antimicrobial gene expression programs. It remains unknown whether there are distinct immune responses to CDNs in Drosophila tissues. Here, we investigated tissue specific CDN-STING responses and uncovered differences in gene-induction patterns across tissues that play important roles in viral infections. Using tissue-and cell-specific genetic studies we found that dSTING in the fat body controls CDN-induced expression of dSTING-regulated gene 1 (Srg1) but not dSTING-regulated gene 2 (Srg2) or 3 (Srg3). In contrast, the gastrointestinal tract largely controls expression of Srg2 and Srg3. We found that Srg3 is antiviral against the natural fly pathogen Drosophila C virus and the human arthropod-borne Rift Valley Fever virus (RVFV), but not other arthropod-borne viruses including Sindbis virus and dengue virus. Furthermore, we found that Srg3 has an important role in controlling RVFV infection of the ovary which has important implications in understanding vertical transmission of viruses and RVFV in mosquitoes. Overall, our study underscores the importance of tissue-specific responses in antiviral immunity and highlights the complex tissue regulation of the CDN-STING pathway.